Stormwater runoff treatment from automobile workshops in Nigeria using combined rice husk, gravel and activated carbon filters. - Ataguba, Clement Oguche (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD) -- Stellenbosch University, 2022.